Protective Role of Terminalia arjuna Seed Extract Formulations Against Cardiotoxicity Induced by Mercuric Chloride in Wister Rats - Jagadeesan, G (International Journal of Pharmaceutical & Biological Archive, 2015)
Protective Role of Terminalia arjuna Seed Extract Formulations Against Cardiotoxicity Induced by Mercuric Chloride in Wister Rats